The concentration of attention and its relationship to the accuracy of the transmission of volleyball players from the sitting position, a descriptive research using the method of correlation studies (Journal of the College of Basic Education, 2022)
The research included five sections:The First Section: Define the research and its importance andforming>The research aimed at knowing the relationship between concentrateattention and its relation with accuracy of dispatching for disabled fromstate of sitting for Wesam Al-Mahjed team in Baghdad.Research Assumption: there is a relation with connected statiscal referencebetween concentrate attention and its relation with accuracy of dispatchingfor disabled from state of sitting.The Second Section: this section included the similar and theoreticalstudies and described the attention and concentrate the attention types ofattention nature of attention process and factors that effected on attentionthe individual differences in attention also accuracy and its types.The third section: Procedures of research, this research contained theapproach of research and the used tools and statistical means the fourthSection: Presentation the result and discussing it and by them we reachedto achieving the purposes.The fifth Section : conclusions and recommendationsThis section included the conclusion the research researched to itthrough his study and the most important are:1-Existence connected relation with moral sign between concentrateattention and the accuracy of dispatching2- There was high concentrate attention and also accuravy in kill ofdispatching.Most important recommendations are:1- Doing similar research in elation with concentrate attention andaccuracy of dispatching and other attack skills.2- Giving enough time during perform skill in order to do it in the rightway.